Revision of the Nasal Dorsum - Moubayed, Sami P.; Most, Sam P. (Facial Plastic Surgery, 2017)
Revision of the dorsum in secondary rhinoplasty is challenging, regardless of the cause. Dorsal deformities should be evaluated for both aesthetic and functional. The authors briefly outline the presentation, etiology, pathogenesis, and treatment choices backed by evidence-based data, when applicable, for the following dorsal revision indications in secondary rhinoplasty: inverted-V and midvault narrowing, overresected dorsum, irregular dorsum, saddle nose, and pollybeak.
Keywords: secondary rhinoplasty; dorsum; revision rhinoplasty